Os princípios didáticos na perspectiva marxista da educação: limites e avanços a partir do estudo de seus fundamentos à luz da Teoria da Subjetividade - Chaves, Naíma de Paula Salgado (2019)
This research presents a typology and a classification of the systems of didactic principles elaborated under the Marxist perspective of education in historical, social, cultural, political contexts and different reports, as well as a critical analysis of those systems based on constructive-interpretive categories formulated in the approach of Subjectivity Theory of Fernando González Rey (1997). The systems of didactic principles correspond to the following authors: the russians Konstantinov, Savich and Smirnov; Savin; Vigotski, A. N. Leontiev and Ya. Galperin presented by Núñez; A. A. Leontiev; Davidov; Danilov; Zankov and Collective of Authors; the germans Klingberg; Collective of Authors; the cubans Labarrere Reyes and Valdivia Pairol; Silvestre Oramas and Zilberstein Toruncha and Mitjáns Martínez and the brazilians J. C. Libâneo; M. Sforni; Franco; Souza; and Longarezi. Thereby, the general objective was to establish, with theoretical, epistemological and methodological rigor, a typology and classification of the different systems of didactic principles and from the study of its philosophical, psychological and pedagogical foundations the critical analysis based on the categories inspired by the Theory Subjectivity: subjectivity, subject, subjective sense, learning-development, symbolic-emotional unity, and dialectic. As a result, it is possible to identify, in these systems of didactic principles, issues as: the marginality of subjectivity from the point of view of the generative character of the subject in the unity of the symbolic-emotional; principles of conditionality and determinism; the denial of the subject as producer of subjective senses; dichotomies between internal and external, individual and social, material and psychic, symbolic and emotional; consciousness as a reflection of reality; the understanding of the activity as a process of internalization of knowledge; and the predominance of the cognitivist character, motivation as punctual content to activate action. From these elements we point out the need to integrate into Didactics: subject as producer and generator of meanings; subjectivity as a process of individual and social production; the unity of the cognitive-emotional; the subjective senses as production of the experience lived in the pedagogical activity; the development-learning unit; the dialectical character of the processes of human production; motivation as subjective production; and the historical, social and cultural character of human activity. As a result of the analysis, we highlight the presentation of the most recurring principles among the seventeen systems for the teaching-learning process and of the three ones for the training of teachers. In summary, a system of didactic principles creates new meanings and senses when the subject is understood by its generative, creative, active, intentional and subjective-producing character, and when the psychological nature of learning is considered inseparable from subjectivity.